Media Literacy and the Emerging Media Citizen in the Nordic Media Welfare State - Forsman Michael (Nordic Journal of Media Studies, 2020)
Since the 1960s, there has been a thriving Nordic tradition of media literacy research, pedagogics, and policy on how to best prepare the emerging media citizen for an increasingly mediatised society. Although the Nordic model of media literacy has previously been characterised by connections to Bildung, critical theory, cultural studies, and progressive pedagogics, much of today's understanding of media literacy is associated with a more instrumental understanding of education, with connections to the commercialisation and digitalisation of compulsory education. By suggesting a historisation of the Nordic media literacy tradition, in connection to the Nordic media welfare state, this article opens a debate about the future directions of Nordic media literacy.